1984
DOI: 10.1007/bf01999962
|View full text |Cite
|
Sign up to set email alerts
|

Morphologie und Ultrastruktur der KoralleCornularia cornucopiae (Anthozoa, Octocorallia)

Abstract: Morphology and ultrastructure of the coral Cornularla cornucopiae (Anthozoa, Octocorallia). Cornularia cornucopiae is a colonial coral whose polyps arise singly from stolons. In contrast with other octocorallia C. cornucopiae lacks calcareous spicules. Therefore, tissue preparation for electron microscopic investigations can be performed. The presence of a calyx such as the theca of hydroids, in which the polyps may be completely retracted, is conspicuous. The calyx consists of three layers. The structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Sections of the attachment foci (Fig. 6b and c) parallel to the skeleton axis are most similar to those found in the octocorallians Leptogorgia virgulata (Tidball, 1982a), Dendronephthya hemprichi (Barneah et al, 2002), Cornularia cornucopia (Benke and Hündgen, 1984), and to desmocytes found in the hexacorallian Stylophora psitillata (Muscatine et al, 1997). …”
Section: Discussionsupporting
confidence: 58%
“…Sections of the attachment foci (Fig. 6b and c) parallel to the skeleton axis are most similar to those found in the octocorallians Leptogorgia virgulata (Tidball, 1982a), Dendronephthya hemprichi (Barneah et al, 2002), Cornularia cornucopia (Benke and Hündgen, 1984), and to desmocytes found in the hexacorallian Stylophora psitillata (Muscatine et al, 1997). …”
Section: Discussionsupporting
confidence: 58%
“…One end of such a rivet is bound to the mesogleal fibrillae, and the other end is embedded in the cuticle adherent to the substrate. Desmocytes found in Octocorallia such as Leptogorgia virgulata (see Tidball 1982) and Cornularia cornucopiae (see Benke & Hundgen 1984) take active part in binding soft tissues onto endoskeletal structures.…”
mentioning
confidence: 99%
“…1a). The ultrastructure of this species has been described in detail (Benke & Hündgen 1984) as well as its cnidome (Schmidt 1981). However, no studies have been dedicated to investigating the ecology and reproductive biology of this species.…”
Section: Introductionmentioning
confidence: 99%